The growing importance of the risk-taking channel in the process of transmitting monetary policy - Redo, Magdalena (Torun International Studies, 2013)
Effectiveness of monetary police depends on proper identification of changes happening in functioning of particular channels which transmit impulses of monetary policy directly into economy. Such changes sometimes limit the importance of certain channels, and sometimes they strengthen other channels, as it occurred in the recent years with risk-taking channels. Globalization, growth of competition, anchoring of low inflation in Western economies, too low economic growth when compared with the issue of unemployment, development of finance market, conscious policy of low interest rates in the USA – all of that contributed to lowering interest rates all over the world, growing the level of acceptable risk, and strengthening the negative correlation between the level of investment based on interest rates and the tendency of risk and, at the same time, operating of a risk-taking channel in the process of transmitting impulses of monetary policy into economy. The main aim of this essay is to familiarize readers with importance of the risk-taking channel in the process of transmitting monetary policy into economy and to overview research confirming growth of its importance in the recent years.